Drug utilization patterns and reported health status in ethnic German migrants (Aussiedler) in Germany: a cross-sectional study - Volodina, Anna; Bertsche, Thilo; Kostev, Karel; Winkler, Volker; Haefeli, Walter E.; Becher, Heiko (BMC public health, 2011)
Inadequate utilization of healthcare services by migrant populations is an important public health concern. Inadequate drug consumption and poor compliance to the therapeutic regimen are common manifestations of low health-care seeking behavior present in migrants even in the countries with well-established healthcare systems. There are few studies on the use of medicines among the different groups of migrants in Germany. The objective of this study is to investigate drug consumption patterns of ethnic German migrants (Aussiedler) and their current health status.
Gesehen am 27.10.2022